2008
DOI: 10.1088/0953-4075/41/11/115401
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric Jones spectroscopy of alkali atoms

Abstract: The Jones effect in a medium of free atoms exposed to static electric and magnetic fields is a useful tool for determining details of an atomic structure. For atoms in their nS ground states irradiated by a monochromatic wave in resonance with a single-photon transition to an n D state, the bilinear Jones effect is not shaded by the quadratic Kerr and Cotton-Mouton effects, nor by the linear in magnetic field Faraday effect. The position and shape of the amplitude resonance may provide information on spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…To our knowledge, up to now this effect has always been observed as a nonreciprocal dichroism [14][15][16], which is related to birefringence through Kramers-Kronig relations. Calculations have been made for atomic gases of alcaline-earth-like atoms near S-P or S-D resonances [10] and alcaline atoms near S-D resonances [11]. All these results are consistent with the expectation that for symmetry reasons, magnetoelectric non-reciprocity (MENR) should have the same order of magnitude as magneto-electric Jones birefringence (MEJB), a birefringence with its eigenaxis oriented at ±45 • with respect to the applied fields.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…To our knowledge, up to now this effect has always been observed as a nonreciprocal dichroism [14][15][16], which is related to birefringence through Kramers-Kronig relations. Calculations have been made for atomic gases of alcaline-earth-like atoms near S-P or S-D resonances [10] and alcaline atoms near S-D resonances [11]. All these results are consistent with the expectation that for symmetry reasons, magnetoelectric non-reciprocity (MENR) should have the same order of magnitude as magneto-electric Jones birefringence (MEJB), a birefringence with its eigenaxis oriented at ±45 • with respect to the applied fields.…”
supporting
confidence: 70%
“…In recent years, magneto-electric Jones dichroism has been observed in two atomic parity violation experiments [4,5], where it may generate systematics. Some calculations performed in atomic gases such as alkaline [11] and alkaline-earth-like atoms [10] have confirmed that bilinear magneto-electro-optical effects are far from negligible near some of the atomic resonances. Static electric and magnetic fields may thus become a novel tool for a fine control of the optical properties of the atomic media used in high precision measurements and metrology.…”
mentioning
confidence: 99%
“…Since our rods provide crossed fields rather than parallel ones as required for Jones birefringence, we will measure the magneto-electric directional anisotropy in Nitrogen, and we therefore expect a slightly different value, probably a few times higher as far as we can infer from various calculations [15][16][17][18]. Comparison with the present 200 µHz sensitivity of our apparatus makes us confident that we should achieve soon the first observation of magneto-electric directional anisotropy in a gas.…”
Section: External Fields Generationmentioning
confidence: 93%
“…Finally, our rods can provide fields B eff = 0.85 T and E = 0.35 MV/m rms on a total length 4L E×B = L 2 = 0.8 m. In such fields, the order of magnitude of the expected frequency modulation due to Jones birefringence in Nitrogen (see Table 1 Since our rods provide crossed fields rather than parallel ones as required for Jones birefringence, we will measure the magneto-electric directional anisotropy in Nitrogen, and we therefore expect a slightly different value, probably a few times higher as far as we can infer from various calculations [15][16][17][18]. Comparison with the present 200 µHz sensitivity of our apparatus makes us confident that we should achieve soon the first observation of magneto-electric directional anisotropy in a gas.…”
Section: External Fields Generationmentioning
confidence: 95%
“…There is not much literature on magneto-electric effects in gases. Jones birefringence has been computed in usual simple gases [14] for non-resonant light, while analytical calculations are available for alcaline-earth atoms [15] and for alcaline atoms [16] in the vicinity of several atomic resonances. It is worth noting that for all the resonances studied, directional anisotropy is slightly larger than linear birefringence.…”
Section: Expected Valuesmentioning
confidence: 99%